2016
DOI: 10.1080/10548408.2016.1260520
|View full text |Cite
|
Sign up to set email alerts
|

A casino-induced satisfaction of needs: scale development and its relationship with casino customer loyalty

Abstract: Based on Maslow's hierarchy of needs, this study develops a five-factor casinoinduced satisfaction of needs scale and examines its relationship with casino customer loyalty using Macau as a study context. The findings show that the respondents' most visited casinos had only marginally met the respondents' various inner needs; there's still ample room for Macau casinos to improve the level of their customers' satisfaction regarding customers' inner needs. Among the five types of inner needs, self-actualization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 66 publications
(82 reference statements)
0
3
0
Order By: Relevance
“…Some authors recognize that the Maslow model is easy to use but object to its absence of flexibility, its lack of cause-to-effect relationships (e.g., between needs and satisfaction), its individualistic if not egoistic foundation, the hierarchy itself (needs can exist concomitantly), and the difficulty of measuring it (Mittelman, 1991). Other authors assert that it only reflects individualistic societies (Tsai et al, 2017). 4 For an in-depth analysis, see Mesly (2021b).…”
Section: Theoretical and Managerial Relevancementioning
confidence: 99%
“…Some authors recognize that the Maslow model is easy to use but object to its absence of flexibility, its lack of cause-to-effect relationships (e.g., between needs and satisfaction), its individualistic if not egoistic foundation, the hierarchy itself (needs can exist concomitantly), and the difficulty of measuring it (Mittelman, 1991). Other authors assert that it only reflects individualistic societies (Tsai et al, 2017). 4 For an in-depth analysis, see Mesly (2021b).…”
Section: Theoretical and Managerial Relevancementioning
confidence: 99%
“…There are exceptions to Maslow's hierarchy of needs (Maslow, 1970;Compton, 2018). For instance, individuals' creativity or high ideals may override basic needs (Maslow, 1970:51-53;Tsai et al, 2017;Compton, 2018), and extreme poverty may lead belonging needs to override safety needs (Tai and Diener, 2011). It is not clear whether patients in these exceptional circumstances would conform to group influence or not.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…The study of inertia and conformity as antecedents to loyalty is important in the context of healthcare because health is a major priority need for human beings. Alongside the importance of healthcare, stability (inertia) and belonging (group conformity) are similarly important needs to human beings (Maslow, 1970; Tsai et al , 2017). Specifically, health and inertia are on the second most important level of human needs (safety/stability), whereas group conformity is on the third most important level (love/belonging).…”
Section: Introductionmentioning
confidence: 99%
“…Most previous customer satisfaction studies have focused on how customers assess product offerings and services presented by the service provider, but have largely overlooked whether or not such products/services satisfy a customer's inner needs; a customer may feel satisfied with a particular product or service (e.g., tasty abalone) but that same product or service may not necessarily satisfy her or his inner needs (e.g., feeling thirsty). One exception to this trend is Tsai et al's (2017) study, which measured customers' casino-induced satisfaction of needs by adopting Maslow's hierarchy of needs. They found that casino customers' safety and security, selfactualization, and physiological needs, if fulfilled by a casino's product offerings and services rendered, positively affected those customers' loyalty to the casino.…”
Section: Introductionmentioning
confidence: 99%
“…The second objective is to identify and assess the potential moderators of this relationship, including gaming attitude, subjective norms, perceived behavioral control, perceived gaming value, and perceived personal luck. Macau has seen exponential growth, both in terms of casino gaming supply and demand, since its gaming liberalization in 2002 (Tsai et al, 2017). While Macau's casino gaming industry has experienced ups and downs due to various internal and external environmental factors, such as the 2008 global financial crisis, the Chinese government's antigraft campaign (Oster, 2014), and the recent COVID-19 pandemic, the industry is still intensely competitive, with the development of mega casino resorts in the pipeline (Blaschke, 2020), in addition to its already competitive casino gaming landscape.…”
Section: Introductionmentioning
confidence: 99%